Integrating Islamic Values into Academic Supervision to Support SDG 4: A Multisite Case Study of Teacher Development in Two Faith-Based Primary Schools - Fitria Hanaris; Yatim Riyanto; Nunuk Hariyati; Mohamad Hisyam Ismail; Windasari Windasari; Noer Risky Ramadhani; Hanandita Veda Saphira (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To investigate the implementation, operational challenges, and strategic outcomes of integrating prophetic virtues into a standardized instructional coaching framework within faith-based primary schools. Method: Employing a qualitative approach with a multisite case study design, this inquiry examined the academic supervision workflows at School A and School B in Indonesia. Data were generated through prolonged fieldwork triangulation, encompassing semi-structured in-depth interviews with 16 key informants (principals, vice-principals, and teachers), non-participant observations of clinical supervision cycles, and institutional document audits. Data were systematically analyzed using the constant comparative method. Results: The findings demonstrate that transforming the secular GROW model into a spiritually responsive